Patient Safety and Pro Re Nata Prescription and Administration: A Systematic Review - Mojtaba Vaismoradi (Pharmacy, 2018)
PRN is the acronym for ‘pro re nata,’ written against prescriptions whose administration shouldbe based on patients’ needs, rather than at set times. The aim of this systematic review was to exploresafety issues and adverse events arising from PRN prescription and administration. Electronic databasesincluding Scopus, PubMed [including Medline], Embase, Cinahl, Web of Science and ProQuest weresystematically searched to retrieve articles published from 2005 to 2017. Selection criteria: we included allrandomized controlled trials (RCTs) and studies with comparison groups, comparing PRN prescriptionand administration with scheduled administration, where safety issues and adverse events were reported.The authors independently assessed titles, abstracts and full-texts of retrieved studies based on inclusioncriteria and risk of bias. Results were summarised narratively. The search identified 7699 articles.Title, abstract and full-text appraisals yielded 5 articles. The included studies were RCTs with oneexception, a pre-test post-test experimental design. Patient populations, interventions and outcomesvaried. Studies compared patient-controlled or routine administration with PRN and one trial assessed theeffect of a practice guideline on implementation of PRN administration. More analgesia was administeredin the patient-controlled than the PRN arms but pain reduction was similar. However, there was littledifference in administration of psychotropic medicines. No differences between patient-controlled andPRN groups were reported for adverse events. The PRN practice guideline improved PRN patienteducation but non-documentation of PRN administration increased. This systematic review suggests thatPRN safety issues and adverse events are an under-researched area of healthcare practice. Variations inthe interventions, outcomes and clinical areas make it difficult to judge the overall quality of theevidence. Well-designed RCTs are needed to identify any safety issues and adverse events associatedwith PRN administration. Available from: ttps://www.researchgate.net/publication/327286136_Patient_Safety_and_Pro_Re_Nata_Prescription_and_Administration_A_Systematic_Review/stats [accessed Aug 30 2018].